(untitled) (Swiss Medical Weekly, 2019)
The earliest attempts at cell therapy can be attributed to Charles-Edward Brown-Séquard (1817–1894), who sought to treat senescence and aging by injecting animal gonad shreds into his contemporaries, a practice that was widespread in late 19th century. Since then, advances in science have enabled the development of biological substitutes to restore the function of various tissues. Skin was one of the first tissues to be regenerated. For severe burns, patient survival depends on the restoration of skin function as a barrier against pathogens and control of body temperature and fluid loss. We aim here to overview the different cell therapy techniques implemented at the University Hospital of Lausanne (CHUV), one of the two Swiss national centres of highly specialised medicine for burn care. In particular, we will describe the specific indications for each of the different therapies as well as future perspectives.